Інтеграція реформ місцевого самоврядування, аграрної політики та публічного управління для відновлення економіки України в умовах децентралізації та європейської інтеграції у повоєнний період - Шпортюк, Наталія Леонідівна; Shportiuk, Natalia (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2025)
Стаття досліджує взаємозв’язок реформ у сферах місцевого самоврядування, аграрної політики та державного управління як ключовий фактор відновлення економіки України. Особливу увагу приділено ролі децентралізації та євроінтеграції у цьому процесі, адже вонисприяють зміцненню демократичних інститутів, підвищенню ефективності державного управління та адаптації економіки до сучасних викликів. Розглядаються питання відновлення інфраструктури, підтримки малого та середнього бізнесу, створення сприятливого інвестиційного клімату, а також забезпечення соціальної стабільності в умовах післявоєнного періоду. Аналізується досвід європейських країн, який може бути корисним для України. На основі отриманих результатів автор формулює практичні рекомендації для державної політики, спрямовані на розбудову сталої економічної моделі та інтеграцію у міжнародний економічний простір. This research delves into the critical intersection of reforms within local governance, agricultural policy, and public administration as pivotal catalysts for Ukraine's economic resurgence in the aftermath of conflict. The study underscores the transformative role of decentralization and European integration, not merely as parallel processes, but as intrinsically linked mechanisms that hold the potential to reshape Ukraine's socio-economic landscape.The analysis commences with a comprehensive examination of the multifaceted challenges confronting Ukraine's economic revitalization. It explores the intricate web of factors that have contributed to the nation's economic fragility, including the devastating impact of conflict, structural imbalances, and the imperative to align with European standards. Central to the investigation is the exploration of how synergistic reforms across local governance, agricultural policy, and public administration can collectively address these challenges. The research posits that a holistic approach, ncompassing institutional strengthening, policy coherence, and effective implementation, is essential to unlock Ukraine's economic potential. The study meticulously dissects the intricacies of local governance reform, emphasizing its potential to empower communities, enhance participatory decision-making, and foster local ownership of development initiatives. It analyzes the devolution of authority and resources to local levels, the strengthening of local representative institutions, and the promotion of civic engagement as crucial components of this reform process. In parallel, the research delves into the complexities of agricultural policy reform, recognizing the agricultural sector's significant contribution to Ukraine's economy. It explores strategies to enhance agricultural productivity, modernize farming practices, diversify agricultural output, and promote sustainable rural development. The study also examines the challenges of land reform, access to finance for farmers, and the need to align with EU agricultural standards. Furthermore, the research scrutinizes the imperative to overhaul public administration, recognizing its pivotal role in facilitating effective governance and efficient service delivery. It analyzes the need for greater transparency, accountability, and responsiveness within public institutions. The study also explores the importance of merit-based recruitment and promotion, capacity building for public officials, and the adoption of digital technologies to enhance public administration efficiency. The research highlights the crucial role of decentralization in empowering local communities to take charge of their development trajectories. It analyzes the transfer of fiscal resources and administrative responsibilities to local authorities, the strengthening of local self-governance mechanisms, and the promotion of inter-municipal cooperation. European integration is examined not only as an external driver of reform but also as an opportunity to align Ukraine's institutional framework and policy landscape with established European norms and standards. The study explores the harmonization of legislation, the adoption of best practices, and the alignment with EU regulatory frameworks across various sectors. The research also delves into the specific challenges of post-conflict reconstruction, recognizing the need to address the physical destruction of infrastructure, the displacement of populations, and the psychological scars of war. It explores strategies for infrastructure rehabilitation, housing reconstruction, economic reintegration of displaced persons, and the provision of social and psychological support services.
Integration of local government, agrarian policy, and public administration reforms for the recovery of Ukraine’s economy under decentralization and European integration in the post-war period
Keywords: децентралізація; decentralization; місцеве самоврядування; local government; післявоєнне відновлення; post-war recovery; державне управління; public administration; європейська інтеграція; European integration; економічний розвиток; economic development; реформи; reforms; інфраструктура; infrastructure; соціально-економічний розвиток; socio-economic development; інституційна спроможність; institutional capacity